1998
DOI: 10.1074/jbc.273.11.6019
|View full text |Cite
|
Sign up to set email alerts
|

MgcRacGAP, A New Human GTPase-activating Protein for Rac and Cdc42 Similar to Drosophila rotundRacGAP Gene Product, Is Expressed in Male Germ Cells

Abstract: In a search for new partners of the activated form of Rac GTPase, we have isolated through a two-hybrid cloning procedure a human cDNA encoding a new GTPase-activating protein (GAP) for Rho family GTPases. A specific mRNA of 3.2 kilobases was detected in low abundance in many cell types and found highly expressed in testis. A protein of the predicted size 58 kDa, which we call MgcRacGAP, was detected in human testis as well as in germ cell tumor extracts by immunoblotting with antibodies specific to recombinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
121
1
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(133 citation statements)
references
References 30 publications
6
121
1
3
Order By: Relevance
“…RacGAP1 is a GTPase-activating protein that has been implicated in controlling cell growth and differentiation (35) and cytokinesis (25) (24,36), and this may depend on its phosphorylation status (37). In contrast, some studies suggest that RacGAP1 is able to mediate some of its functions independently of its GAP activity (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RacGAP1 is a GTPase-activating protein that has been implicated in controlling cell growth and differentiation (35) and cytokinesis (25) (24,36), and this may depend on its phosphorylation status (37). In contrast, some studies suggest that RacGAP1 is able to mediate some of its functions independently of its GAP activity (38).…”
Section: Discussionmentioning
confidence: 99%
“…Previous microarray data demonstrated that Rac-GAP1 (also known as MgcRacGAP) is down-regulated in hESCs after exposure to trophoblast-conditioned medium (23). We analyzed RacGAP1 expression in hESCs to determine whether the embryo-induced increase in hESC Rac1 activity that we observed in vitro resulted from localized inhibition or down-regulation of RacGAP1, which, in other cell types, inactivates Rac1 (24). Western blot analysis showed that RacGAP1 is expressed in hESCs and in human endometrial epithelial cells, JEG3 choriocarcinoma cells, and placental tissue (Fig.…”
Section: Levels Of Hesc Racgap1 Are Decreased Locally In Response To Thementioning
confidence: 99%
“…However, in vitro the Rho GAP activity of MgcRacGAP is relatively limited. (50,51) It has been reported that phosphorylation of MgcRacGAP by Aurora B kinase stimulates its Rho GAP activity, (52) and given that this kinase is activated prior to the onset of cytokinesis and localizes in the same general region as MgcRacGAP, (53) this could contribute to GTPase flux. However, based on structural considerations, the relevance of this phosphorylation event has been questioned.…”
Section: Gtpase Fluxmentioning
confidence: 99%
“…Initial evidence indicated that this GAP is significantly more active in vitro toward Rac, another member of the Rho family of GTPases, rather than RhoA (Toure et al 1998;JantschPlunger et al 2000). Subsequently, genetic studies in Drosophila and C. elegans also suggested that RacGAP1 could inactivate Rac GTPases in vivo (D'Avino et al 2004;Canman et al 2008), and this would inhibit the formation of a branched actomyosin web and, therefore, reduce stiffness at the equatorial cortex ( Fig.…”
Section: Cleavage Furrow Ingression: Actomyosin Filaments Take Centermentioning
confidence: 99%